2008
DOI: 10.1159/000156471
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Growth Hormone Treatment on Lymphocyte Functions in Old Male Rats

Abstract: Introduction: Age-related changes in the communication between the neuroendocrine and the immune system have been scarcely studied. Aging in mammals is associated with an impairment of the immune response, especially regarding lymphocyte functions. Furthermore, the endocrine system is also affected by aging, one of the most significant changes being the decrease in the secretion of several hormones such as growth hormone (GH). Objective: The aim of the present work was to study whether GH replacement therapy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 89 publications
(42 reference statements)
1
7
0
1
Order By: Relevance
“…GH therapy in elderly rats is able to decrease fat tissue and to increase lean body mass, besides improving the content of plasma lipids, bone density, stimulating skeletal muscle protein synthesis and possibly inhibiting protein degradation via stimulation of IGF-I (Nass et al 2009;Castillo et al 2005b). A beneficial effect in several parameters related with the immune function, such as chemotaxis, natural killer activity and limphoproliferation has been also observed by our group thus delaying some aspects of immunosenescence (Baeza et al 2008).…”
Section: Introductionsupporting
confidence: 58%
“…GH therapy in elderly rats is able to decrease fat tissue and to increase lean body mass, besides improving the content of plasma lipids, bone density, stimulating skeletal muscle protein synthesis and possibly inhibiting protein degradation via stimulation of IGF-I (Nass et al 2009;Castillo et al 2005b). A beneficial effect in several parameters related with the immune function, such as chemotaxis, natural killer activity and limphoproliferation has been also observed by our group thus delaying some aspects of immunosenescence (Baeza et al 2008).…”
Section: Introductionsupporting
confidence: 58%
“…In contrast, in experiments with 24 month old Wistar rats, rhGH replacement therapy (2 mg/kg daily for 10 weeks) significantly improved several lymphocyte functions such as NK cell activity (Baeza, et al, 2008). Interestingly, a previous study confirmed that both total NK cell count and particularly CD16 + NK cell subtype were reduced in GHD patients compared to controls (Sneppen et al, 2002).…”
Section: Discussionmentioning
confidence: 88%
“…GH up-regulates the production of NO and TNF-α by murine peritoneal macrophages [83] and IGF-1 stimulates production of TNF-α by human monocytes [91]. GH treatment reverses ageing-related reductions of leucocyte chemotaxis, mitogen-induced lymphoproliferation and NK cell activity in male [93] and female [94] rats, with particularly marked effect in ovariectomized animals. GH treatment reverses ageing-related reductions of leucocyte chemotaxis, mitogen-induced lymphoproliferation and NK cell activity in male [93] and female [94] rats, with particularly marked effect in ovariectomized animals.…”
Section: Other Hormones Of Potential Significancementioning
confidence: 99%